2018
DOI: 10.1093/eurheartj/ehx799
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural myocardial infarction and injury in elective coronary stenting

Abstract: Periprocedural MI and injury are frequent complications of elective PCI associated with an increased rate of cardiovascular events at 30 days and 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
130
2
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 31 publications
3
130
2
19
Order By: Relevance
“…The latter study was limited by a small number of events (n=20) confined to a 3-month follow-up period; it included patients with stable CAD as well as recent acute coronary syndromes; and used earlier, less sensitive troponin assays. 22 A recent study by Zeitouni et al 17 in 1390 elective PCI patients found a higher rate of 1-year cardiovascular events in patients with PMI according to the Universal Definition of MI criteria, that is, hs-cTnT rise above 5× URL and additional clinical evidence of myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter study was limited by a small number of events (n=20) confined to a 3-month follow-up period; it included patients with stable CAD as well as recent acute coronary syndromes; and used earlier, less sensitive troponin assays. 22 A recent study by Zeitouni et al 17 in 1390 elective PCI patients found a higher rate of 1-year cardiovascular events in patients with PMI according to the Universal Definition of MI criteria, that is, hs-cTnT rise above 5× URL and additional clinical evidence of myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found a higher incidence of PMI, up to 5.5% using the CK-MB-based SCAI definition 8,9 or up to 13.3% using the second and third Universal Definition of MI (ie, based on lower biomarker thresholds and ancillary criteria of myocardial ischemia). 16,17 These findings indicate marked heterogeneity in the diagnosis of PCI-related MI, depending on the biomarker used and cutoff values applied, as well as the presence or absence of clinical signs or symptoms across various definitions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reducing the number of complications during PCI may improve the clinical outcomes of PCI. pMI is a complication of PCI whose mechanism is thought to be related to side branch occlusion, atherosclerotic embolism, or both during PCI and may be associated with cardiovascular events after PCI [2,3]. The present study shows that novel 3D evaluation of coronary plaques using noncontrast T1w imaging could facilitate the prediction of pMI after elective PCI.…”
Section: Discussionmentioning
confidence: 69%
“…Although technical advances in PCI have resulted in a safer therapeutic procedure, 5-30% of patients undergoing elective PCI demonstrate evidence of periprocedural myocardial injury (pMI) from the procedure itself [1,2]. The extent of pMI as determined by evaluation of creatine phosphokinase MB isoenzyme, high-sensitivity troponin T (hs-cTnT), and troponin I is significant enough to be prognostically important [1,3]. Therefore, pMI might reduce some of the beneficial effects of coronary revascularization.…”
Section: Introductionmentioning
confidence: 99%
“…21 In a second paper entitled 'Periprocedural myocardial infarction and injury in elective coronary stenting', Johanne Silvain and colleagues from the Université Paris 6 Sorbonne in Paris, France assessed the incidence, risk factors, and prognosis of periprocedural myocardial infarction and myocardial injury in patients undergoing elective percutaneous coronary intervention (PCI). 22 Of the 1390 undergoing elective PCI, the primary endpoint of myocardial infarction, stent thrombosis, and myocardial injury occurred in 29% of patients. Independent risk factors for the primary endpoint were left main PCI, total stent length of >30 mm, multiple stenting, chronic kidney disease, and age above 75 years.…”
mentioning
confidence: 99%